Gender-Inclusive Rural Tourism: Women’s Participation in the Panji Ecovillage Homestay, North Bali - Dini Andiani, Nyoman; Artini , Luh Putu; Yogiswari, Ni Made Mas; Adhitra , Andris; Banhidi , Miklos (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
Women of the Farmers Group in Panji Village, North Bali, do not only support their families through agricultural work but also convert spare rooms in their homes into homestays, forming the Women Ecovillage Homestay Group. Through this community, they learn collectively to engage in and benefit from village tourism. This initiative illustrates how rural women contribute simultaneously to economic improvement and cultural preservation. This study examines their roles in community-based tourism (CBT) and their contribution to small-scale sustainable tourism, emphasizing gender-inclusive village development. Fieldwork was carried out intermittently from 2023 to 2025 as part of a community service program, enabling continuous observation of participation and empowerment processes. Using action research, the researcher applied and tested strategies developed through FGDs with key stakeholders. The findings show that women in Panji Village play a central role in sustaining tourism by managing homestays while safeguarding cultural identity, offering a model for inclusive and gender-responsive rural tourism development.